An Exploration of Oral-Gut Pathogens Mediating Immune Escape of Pancreatic Cancer via miR-21/PTEN Axis - Li, Rui; Hu, Yaoyuan; Hou, Shuhong (Frontiers in Microbiology, 2022)
Oral-gut pathogens are closely associated with pancreatic cancer, such as Campylobacter jejuni, Clostridium difficile, Enterococcus faecalis, Escherichia coli, Fusobacterium nucleatum, Helicobacter pylori, Porphyromonas gingivalis and Vibrio cholerae, but the related mechanisms remain not well understood. Phosphatase and tensin homolog (PTEN, a widely known tumor suppressor) play a key role in the anti-cancer immune system. Pancreatic cancer cells with PTEN loss are often in the immunosuppressive tumor microenvironment regulated by myeloid-derived suppressor cells (MDSCs), regulatory T cells (Tregs) and M2 macrophages, which is regarded as the mechanism in the immune escape of cancers. miR-21, as an oncogene in human cancers, plays an important role in pancreatic cancer progression, downregulates the levels of PTEN, and may promote cancer to evade host immune surveillance. Some oral-gut pathogens have been found to promote miR-21 expression and reduce PTEN expression. On the other hand, the most gut pathogens infection is thought to produce ROS or activate inflammatory cytokines, which may also induce ROS-mediated miR-21 expression. These pathogens infection is involved with cell density of MDSCs, Tregs and M2 macrophage. Therefore, it is quite reasonable to propose that oral-gut pathogens possibly promote pancreatic cancer escaping from host immune surveillance by activating miR‑21/PTEN axis and immune suppressive cells. The present exploration suggests that increased understanding of the pattern of the effects of gut pathogens on miR‑21/PTEN axis will lead to better insights into the specific mechanisms associated with the immune escape of pancreatic cancer caused by oral-gut microbiota.